The Impact of Concurrent Engineering Strategy on New Compex Product Development Process in Organization: An Empirical Study of Manufacturing and Service Industry in Malaysia (Sains Humanika, 2013)
Taking into account the customers, supplier and organization involvement in the new product development (NPD), this article focuses on the synthesis, evaluation, and selection of various sub-factors of concurrent engineering involved in new product development process. The aim of this study was to provide the reliability and validity of six sub-factors of concurrent engineering model of the 49-item questionnaire and to analyze its association with concurrent engineering and new product development process in a sample of 35 manufacturing and services organization located in Johor, Malaysia. Methods: A self reported survey was conducted in 35 manufacturing and services organization located in Johor, Malaysia. Results: Appropriate internal consistencies of the six sub-scales: customers relationship, team development, continuity, tools and techniques, suppliers involvement and corporate focus and their association with concurrent engineering, were obtained. Zero-order correlation and regressions analysis replicated the theoretically assumed structure of the effective concurrent engineering (ECE). Evidence of criterion validity was obtained from cross-correlations of the scales and from their linear and multiple regression analysis. Finally, all seven scales were associated with a highly significant ratio of concurrent engineering as predicted by fundamental theory. Conclusion: Based on the results of this study the seven version of the model, questionnaire is considered a reliable and valid instrument for measuring association in developing the new complex product development process.
Keywords: Concurrent engineering; new product development; customer satisfaction